2017
DOI: 10.1073/pnas.1705372114
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of huntingtin at residue T3 is decreased in Huntington’s disease and modulates mutant huntingtin protein conformation

Abstract: SignificanceThe findings in this manuscript report on the identification of a posttranslational modification in the huntingtin protein (phosphorylation on residue T3 in the N17 region of the protein), which can revert the conformational effects of the Huntington’s disease (HD) mutation itself on the huntingtin protein and inhibit its aggregation properties in vitro. Using the first ultrasensitive immunoassay for a posttranslational modification of huntingtin protein, we demonstrate that pT3 levels are decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 78 publications
4
78
0
Order By: Relevance
“…We observed that worms expressing mutant HTTN513-YFP (Q128) showed less phosphorylation at 18 T3 and S13 than worms expressing wild-type HTTN513-YFP (Q15) ( Fig. 5B-C), consistent with the previous reports in animal models of HD and patient-derived cells Atwal et al, 2011;Cariulo et al, 2017;Cristina Cariulo, 2019). Importantly, the detection of pT3 and pS13 HTT in C. elegans clearly indicates that this organism expresses kinases capable of phosphorylating these HTT epitopes.…”
Section: Tbk1 Overexpression Modulates Hd Pathology In C Eleganssupporting
confidence: 90%
“…We observed that worms expressing mutant HTTN513-YFP (Q128) showed less phosphorylation at 18 T3 and S13 than worms expressing wild-type HTTN513-YFP (Q15) ( Fig. 5B-C), consistent with the previous reports in animal models of HD and patient-derived cells Atwal et al, 2011;Cariulo et al, 2017;Cristina Cariulo, 2019). Importantly, the detection of pT3 and pS13 HTT in C. elegans clearly indicates that this organism expresses kinases capable of phosphorylating these HTT epitopes.…”
Section: Tbk1 Overexpression Modulates Hd Pathology In C Eleganssupporting
confidence: 90%
“…The observation that phosphomimetic mutations at serine 13 and 16 attenuate disease progression and accumulation of Htt aggregates in the BACHD mouse model highlights the potential role of phosphorylation in regulating Htt function in health and disease and underscores the critical importance of achieving a more in-depth understanding of the effects of phosphorylation at these residues (31). The knowledge gained from such studies could have important implications for the development of novel therapies and diagnostic strategies based on modulating and/or assessing the levels of phosphorylation at these residues (63). Toward these goals, we utilized protein semisynthetic strategies that were recently developed by our group to generate wildtype and expanded forms of exon1 of the huntingtin protein phosphorylated at S13, S16 or both residues.…”
Section: Discussionmentioning
confidence: 98%
“…Phosphorylation of proteins implicated in neurodegenerative diseases such as Tau in Alzheimer's disease, α-synuclein in Parkinson's disease and TDP-43 in Amyotrophic lateral sclerosis seems to correlate with the formation of pathological aggregates and disease progression (62). In Huntington's disease, phosphorylation of N-terminal serine and threonine residues has been detected in human brains, transgenic models and cell culture models of HD (5,31,63,64). However, the role of phosphorylation in regulating the structure, aggregation and HD pathology remains poorly understood, primarily due to the lack of tools that enable site-specific and efficient modulation of phosphorylation in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…HTT is a large protein of ~ 350 kDa that plays critical functional roles in gene expression regulation (Valor ), vesicle transport (Harjes and Wanker ) and autophagy (Ochaba et al ). It is modified post‐translationally at multiple sites (Cariulo et al ; Harding et al ) and gets cleaved by various proteases (Sanchez Mejia and Friedlander ), leading to the release of N‐terminal fragments with an expanded polyQ sequence, which have a high propensity to misfold and self‐assemble into fibrillar aggregates (Scherzinger et al ; Trepte et al ). As a consequence, intranuclear inclusions are formed in neurons.…”
Section: Abnormal Interactions Are Commonly Found In Genetic Diseasesmentioning
confidence: 99%